Market development and policy issues for agri-derivatives in India: a study of cotton and mentha - Tarunika Jain Agrawal; Sanjay Sehgal; Muneesh Kumar (Agricultural Economics Research Review, 2023)
This study of cotton and mentha derivatives aims to analyse the information efficiency of the Indian agri-commodity derivatives market. We find weak information linkages: the cotton spot market dominates in price discovery and its futures market in volatility spillover, and the futures market leads the spot market for both price discovery and risk hedging for mentha. To develop the market and improve the transmission of information, it is necessary to build a physical spot market and integrate it with the derivatives market, create awareness, build institutional capacity, improve delivery-based support, and redesign contract specifications.